Distortive effects of dividend taxation - Tobias Lindhe; Jan Södersten (Uppsala University, Department of Economics, 2013)
This paper examines how the distortions caused by dividend taxation depend on whether or not shareholders can recover their original equity injections without being subject to the dividend tax. We point out the alternative assumptions in the literature on this, and we compare two different tax regimes, one where it is impossible for the firm to pay cash to its shareholders that is not taxed as dividends, the other where the shareholders are allowed a tax-free return of the original capital contributed through new issues. Our analysis shows that the regimes imply a substantial difference to our perceptions of the distortive effects of dividend taxation.
urn:nbn:se:uu:diva-206751
Keywords: H24; H25; H32; 330; Self-employment; dividend taxation; share repurchases; equity trap; cost of capital; nucleus theory; growth path